The Analysis of Ellipsis in A Pair of Silk Stockings A Short Story by Kate Chopin - Karin, Juliana; Juanda (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The title of the research is The Analysis of Ellipsis in “A Pair of Silk Stocking” A Short Story by Kate Chopin. The writer wants to find out what ellipsis features are used and how they are expressed in the short story. The research methodology is descriptive, which means the author analyzes this research by reading the entire short story, analyzing sentence by sentence, classifying ellipsis, and classifying sentences containing ellipsis. The data found in the short story include nominal ellipsis, clausal ellipsis, and verbal ellipsis as the following examples. The writer discovered 27 ellipsis in the short story. The total number of times nominal ellipsis used is 16, with a percentage of 59.26%. Clausal ellipsis was discovered 4 times, with a percentage of 14.81%. Verbal ellipsis with a percentage of 25.93%, the use of verbal ellipsis was discovered 7 times. The impact of this research is that in a fictional writing the sentence structure is more communicative when there is ellipsis in the structure. A literary writer can implement communicativeness in conveying the storyline so that it is not rigid, through the process of ellipsis in a speech